Splenorenal Collaterals as Hallmark for a Twisted Wandering Spleen in a 14-Year-Old Girl with Abdominal Pain: A Case Report - Rashidi Rellum; Gerard Risseeuw; Ivo de Blaauw; Maarten Lequin (Georg Thieme Verlag KG, 2014)
Abstract Wandering spleen is a rare cause of acute or chronic recurrent abdominal pain with a risk of splenic torsion and infarction. We describe a case of a 14-year-old girl with chronic recurrent abdominal pain with a palpable spleen in normal position on the initial physical examination. Laboratory findings were normal. A normal blood flow was seen on the initial (color Doppler) sonography. Magnetic resonance imaging showed an enlarged spleen in the pelvic region with torsion of hilar pedicle and splenorenal collaterals. Semielective, a laparoscopic splenopexy was performed without complications. A twisted wandering spleen should be included in the differential diagnosis of recurrent abdominal pain despite possible normal positioning of the spleen. The presence of splenorenal collaterals on imaging techniques can be used as a diagnostic hallmark.